Pelaksanaan Kewenangan Dinas Kelautan Dan Perikanan Provinsi Kepulauan Riau Dalam Pengelolaan Wilayah Pesisir Dan Pulau-Pulau Kecil: Indonesia - Ramadhan, Muhammad Ilham; Budiman, Shahril (Interaktif : Jurnal Ilmu-Ilmu Sosial, 2022)
The purpose of the study was to determine the Management of Coastal Areas and Small Islands in the Riau Archipelago Province. In this study the theory used by Terry (in Hasibuan, 2012: 3). The population in the study amounted to 5 people, the data analysis used in this study was a qualitative descriptive data analysis technique. Based on the results of the study, it can be analyzed that the Coastal Areas and Small Islands in the Riau Archipelago Province have been managed well, although there are still problems related to coastal areas. Riau Islands Province as a coastal area is an ecosystem that is under threat due to waste pollution scattered in the sea area. Garbage floating in coastal areas causes problems in coastal water boundaries. The garbage can easily come into contact with aquatic animals, humans, boats, fishing nets and so on. Coastal communities also tend to lose their source of life and livelihood. Thus the coastal area requires maximum waste management. The coastal area waste management runs optimally requires government intervention in the form of supervision. Supervision is a management function that is closely related to the achievement of organizational goals, so that supervision in any organization is absolutely necessary. Suggestions that can be submitted are that the marine and fisheries service of the Riau Islands Province needs to formulate sustainable activities in the Coastal Zone and Small Islands in the Riau Archipelago Province. There are sanctions for people who manage coastal areas and small islands that are not in accordance with existing rules and policies.